Customização agregando valor às peças de brechó - Bellintani, Carolina Pereira (2015)
This paper presents a study on the thrift store, trying to contextualize it through social, political and economic movements. From this study, the aim of this work will be targeted through a qualitative research, understanding consumer behavior of thrift store clothes and alternatives for valuing this type of clothing. Valuation techniques relevant in this work are the processes known in the development of customization.